2016
DOI: 10.1002/2016gc006438
|View full text |Cite
|
Sign up to set email alerts
|

A computationally efficient spectral method for modeling core dynamics

Abstract: An efficient, spectral numerical method is presented for solving problems in a spherical shell geometry that employs spherical harmonics in the angular dimensions and Chebyshev polynomials in the radial direction. We exploit the three‐term recurrence relation for Chebyshev polynomials that renders all matrices sparse in spectral space. This approach is significantly more efficient than the collocation approach and is generalizable to both the Galerkin and tau methodologies for enforcing boundary conditions. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 52 publications
0
24
0
Order By: Relevance
“…This system is gravitationally unstable and drives buoyant convective flows across the fluid layer that advect both heat and momentum. We describe this system generally throughout this paper, but it can be thought of as an extended plane layer [14], a finite cylinder [15], or a spherical shell of fluid [16].…”
Section: Introductionmentioning
confidence: 99%
“…This system is gravitationally unstable and drives buoyant convective flows across the fluid layer that advect both heat and momentum. We describe this system generally throughout this paper, but it can be thought of as an extended plane layer [14], a finite cylinder [15], or a spherical shell of fluid [16].…”
Section: Introductionmentioning
confidence: 99%
“…At this stage, any single term that enters the above equation can be written as the product x q ∂ p f /∂x p , where p and q are positive integers. Following Marti et al (2016), this equation is then integrated by parts until no differential operator remains, such that each term has the following form…”
Section: Semi-discrete Formulationmentioning
confidence: 99%
“…The internal matrix elements are determined using the freely available python package developed by Marti et al (2016) ‡ that allows the symbolic computation of those operators § . Excluding boundary conditions, A I m , B I m and C I correspond to band matrices with pu super-diagonals and p sub-diagonals that have a bandwidth defined by…”
Section: Semi-discrete Formulationmentioning
confidence: 99%
“…We adopted the PETSc/SLEPc approach because PETSc is already installed on Cray machines (although the version we use in these experiments is a later version due to a number of important bug fixes that have not yet been merged into the Cray official release), fairly ubiquitous in HPC, known to work well and the flexibility provided by these libraries is important. SLEPc has also been demonstrated to work well in a variety of application areas including engineering, materials science, structural analysis, Earth sciences, and geomagnetism . This last use case is important because it is the same research area as the MEME model and as such SLEPc has already demonstrated benefit in the domain of geomagnetism.…”
Section: Background and Related Workmentioning
confidence: 99%